2018
DOI: 10.1007/s00424-018-2108-1
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1-7)-induced Mas receptor activation attenuates atherosclerosis through a nitric oxide-dependent mechanism in apolipoproteinE-KO mice

Abstract: Angiotensin (Ang)-(1-7) ameliorates vascular injury by increasing nitric oxide (NO) bioavailability. Evidence that Ang-(1-7) attenuates the development of atherosclerosis through a NO-dependent mechanism is still missing. Moreover, it has been postulated that Ang-(1-7) may mediate its effects by other mechanisms than Mas receptor activation. To investigate Ang-(1-7)-dependent Mas receptor function, we treated apoE-KO and apoE/Mas-KO mice chronically with Ang-(1-7) (82 μg/kg per hour) or saline for 6 weeks. Flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Pathomechanisms identified in this study could act in concert with already established B2 and/or AT1 receptor-dependent atherogenic activities. Notably, the following mechanisms mediated by the B2 and/or AT1 receptor could play a direct or indirect role in B2 bradykinin receptor-enhanced atherosclerosis: (I) The B2 bradykinin receptor could promote atherosclerosis by the reduced activation of atheroprotective AT1-inhibitory receptors, AGTR2 and MAS1 (34, 5052), which are directly down-regulated by the B2 bradykinin receptor and angiotensin II AT1 receptor (34, 53) and indirectly dampened via angiotensin II AT1-mediated ACE2 down-regulation (54). (II) In addition, the B2 bradykinin receptor could enhance atherogenesis by decreasing the expression of the vasculoprotective endothelial Kruppel-like factor 4, KLF4 (55), which is directly downregulated by angiotensin II AT1 stimulation [(56); NCBI GEO dataset GSE19286 in Abd Alla et al (7)], and indirectly down-regulated by reduced Mas receptor activation (57).…”
Section: Discussionmentioning
confidence: 99%
“…Pathomechanisms identified in this study could act in concert with already established B2 and/or AT1 receptor-dependent atherogenic activities. Notably, the following mechanisms mediated by the B2 and/or AT1 receptor could play a direct or indirect role in B2 bradykinin receptor-enhanced atherosclerosis: (I) The B2 bradykinin receptor could promote atherosclerosis by the reduced activation of atheroprotective AT1-inhibitory receptors, AGTR2 and MAS1 (34, 5052), which are directly down-regulated by the B2 bradykinin receptor and angiotensin II AT1 receptor (34, 53) and indirectly dampened via angiotensin II AT1-mediated ACE2 down-regulation (54). (II) In addition, the B2 bradykinin receptor could enhance atherogenesis by decreasing the expression of the vasculoprotective endothelial Kruppel-like factor 4, KLF4 (55), which is directly downregulated by angiotensin II AT1 stimulation [(56); NCBI GEO dataset GSE19286 in Abd Alla et al (7)], and indirectly down-regulated by reduced Mas receptor activation (57).…”
Section: Discussionmentioning
confidence: 99%
“…The non‐classical axis consists of ACE2 converting Ang II into Ang (1‐7), a heptapeptide that stimulates the Mas oncogene receptor (MasR) expressed on blood vessels . Numerous experimental studies have shown that Ang (1‐7) exerts a vasoprotective role by increasing NO bioavailability possibly through the MasR resulting in improved vasodilation . Additionally, ACE2 produces alamandine through the conversion of Ang A .…”
Section: Renin Angiotensin System (Ras)mentioning
confidence: 99%
“…This results in decreased circulation levels of a subtype of T cells, neutrophils and macrophages ( 93 ). To research Ang-(1-7)-dependent Mas receptor function, Yang et al used apoE-KO and apoE/Mas-KO mice with Ang-(1-7) or saline for 6 weeks ( 94 ). To check whether Ang-(1-7) regulates atherosclerosis through a NO-dependent pathway, apoE-KO mice were used with the NO synthase inhibitor in the presence or lack of Ang-(1-7) ( 94 ).…”
Section: New Pharmacological Approaches For Rasmentioning
confidence: 99%
“…To research Ang-(1-7)-dependent Mas receptor function, Yang et al used apoE-KO and apoE/Mas-KO mice with Ang-(1-7) or saline for 6 weeks ( 94 ). To check whether Ang-(1-7) regulates atherosclerosis through a NO-dependent pathway, apoE-KO mice were used with the NO synthase inhibitor in the presence or lack of Ang-(1-7) ( 94 ). Ang-(1-7) has been shown to have protective vascular effects through Mas receptor activation ( 94 ).…”
Section: New Pharmacological Approaches For Rasmentioning
confidence: 99%
See 1 more Smart Citation